Unravelling the mechanism of electrochemical degradation of PANI in supercapacitors: achieving a feasible solution - Sekar, Pandiaraj; Anothumakkool, Bihag; Vijayakumar, Vidyanand; Lohgaonkar, Apurva; Kurungot, Sreekumar (Chemelectrochem, 2016)
Herein, we have investigated the mode of electrochemical degradation of polyaniline (PANI) when it was utilized as electrodes for supercapacitors. The PANI-based electrodes in supercapacitor devices were biased at a constant potential of 0.80 V, and the performance characteristics and property changes were carefully investigated as a function of the difference in the polarity of the electrodes. Subsequent to this, the analysis of the individual electrodes [positive (POS-PANI) and negative (NEG-PANI)] shows that the degradation mainly occurs at POS-PANI in comparison to NEG-PANI. Moreover, NEG-PANI retains a maximum capacitance of 510 Fg(-1), with a low charge-transfer resistance (R-CT) of 1.84 Omega and similar redox behavior in comparison to the fresh PANI (f-PANI). In contrast to this case, POS-PANI shows significant loss in capacitance (250 Fg(-1)) and increase in R-CT (3.5 Omega) with a disappearance of the characteristic redox behavior normally displayed by PANI. Furthermore, the drastic drop in the electrical conductivity for POS-PANI (1.2 Scm(-1)) compared to f-PANI (3.4 Scm(-1) and NEG-PANI (2.4 Scm(-1)) shows that the degradation of PANI occurs mainly at the anode (POS-PANI) and, thus, contributes to reduce the net performance of the cell. Hence, to ensure this potential-induced degradation of PANI in supercapacitors and also to promote the system stability, we made an asymmetric supercapacitor (ASC) by keeping PANI as a negative electrode and using carbon as a positive electrode. The derived system is found to display stable capacitance behavior before and after the potential application, in contrast to the ASC fabricated by using conventional method, that is, by keeping PANI as the positive electrode and carbon as the negative electrode. Furthermore, the durability analysis of the prototype solid-state ASC shows an enhanced durability of 27000 cycles with excellent columbic efficiency. The findings of the present study will be helpful in the development of highly stable supercapacitors and other similar energy systems when a material like PANI should be utilized for the electrode applications.
Keywords: asymmetric supercapacitors; cycle stability; electrochemical degradation; polarization; redox chemistry